2004
DOI: 10.1111/j.1469-8749.2004.tb00458.x
|View full text |Cite
|
Sign up to set email alerts
|

International Classification of Functioning, Disability and Health in a cohort of children with cognitive, motor, and complex disabilities

Abstract: The recently endorsed World Health Organization (WHO) International Classification of Functioning, Disability and Health (ICF) is proposed as a new tool to describe human functioning and health in a multiprofessional approach for individuals of all ages. Its application to paediatric neurorehabilitation may be of great help, especially in children with complex disabilities. However, experience with its application in this field is still limited. We tested the application of ICF in 40 children (26 males, 14 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Limitations in classifying functioning in young children by the ICF are described in a few other papers [4,5,36]. Battaglia et al [36] found difficulties in using the ICF checklist, particularly because the checklist included items that were not relevant for younger children and also some items that were inappropriately described to cover the developmental aspect of a function.…”
Section: Linking the Item Content Of The Pedi To The Icfmentioning
confidence: 97%
See 1 more Smart Citation
“…Limitations in classifying functioning in young children by the ICF are described in a few other papers [4,5,36]. Battaglia et al [36] found difficulties in using the ICF checklist, particularly because the checklist included items that were not relevant for younger children and also some items that were inappropriately described to cover the developmental aspect of a function.…”
Section: Linking the Item Content Of The Pedi To The Icfmentioning
confidence: 97%
“…Battaglia et al [36] found difficulties in using the ICF checklist, particularly because the checklist included items that were not relevant for younger children and also some items that were inappropriately described to cover the developmental aspect of a function. A draft version of the ICF for children and youth (ICF-CY) is currently undergoing field trial [37].…”
Section: Linking the Item Content Of The Pedi To The Icfmentioning
confidence: 99%
“…This condition demands comprehensive rehabilitation using age-appropriate tasks and activities [3] which encompass aspects of body function and structure, activity and participation and personal and environmental factors [4].…”
mentioning
confidence: 99%
“…Although ICF was primarily designed for the adult population the model has been used in studies, reports and papers addressing childhood disability (Battaglia et al 2004;Beckung and Hagberg 2002;McConachie et al 2006;McDougall and Miller 2003;Simeonsson et al 2003;Simeonsson, McMillen, and Huntingdon 2002) where it is reported to provide a useful framework for defining domains and describing chronic disability. However, some important aspects of children's activities, such as play, were found to be lacking.…”
Section: The International Classification Of Functioning Disability mentioning
confidence: 98%